Physical, chemical and structural attributes of soil in agroecosystems in the Brazilian Semiarid region - da Rocha Mendes, Kellyane; Cruz Portela, Jeane; Emanuel Fernandes Gondim, Joaquim; Alves Ribeiro, Matheus; Francismar de Medeiros, José; Carvalho Maia de Queiroz, Gabriela (Revista Ciência Agronômica, 2021)
The soil attributes can be easily changed according to its management and use, compromising the productive capacity of theareas. The objective of this research was to evaluate the variability and interrelationships of soil physical, chemical and structural attributes inagroecosystems in the Brazilian Semiarid region (Rio Grande do Norte State), pointing out the most sensitive attributes in the environmentdistinction through multivariate analysis. The research was carried out in the rural community of Piracicaba, Upanema municipality, Rio Grandedo Norte State, Brazil. Four agroecosystems were selected: Native Forest Area (ANF), Corn Bean Consortium Area (ACBC), Pasture Area(AP) and Cashew Area (AC). Undisturbed and deformed soil samples were collected in the 0.00-0.10, 0.10-0.20 and 0.20-0.30 m layers,and the physical, chemical and structural attributes were analyzed. The data were submitted to multivariate statistical techniques, usingthe correlation matrix, cluster analysis, factor analysis and principal component analysis. Factorial analysis revealed the most sensitiveattributes in distinguishing agroecosystems: microporosity, fi eld capacity (FC), permanent wither point (PWP), available water (AW),sand, clay, fl occulation degree (GF), Ca2+, Mg2+ and sum of bases (SB) (F1) and soil density (SD), total porosity (PT), macroporosity,electrical conductivity (EC) and total organic carbon (TOC) (F2). Cluster analysis formed three distinct groups. The TOC was discriminantto group the native forest and cashew tree areas, showing the infl uence of soil management. The other environments were groupedaccording to the texture differentiation, infl uencing the attributes variability.